Downlink Space-Frequency Preequalization Techniques for TDD MC-CDMA Mobile Radio Systems. Issue 1 (29th July 2004) - Silva, Adão; Gameiro, Atílio
Abstract : The paper considers downlink space-frequency preequalizations techniques for time division duplex (TDD) MC-CDMA. We consider the use of antenna arrays at the base station (BS) and analytically derive different preequalization schemes for two different receiver configurations at the mobile terminal: a simple despread receiver without channel equalization and an equal-gain combiner (EGC) conventional receiver. We show that the space-frequency preequalization approach proposed allows to format the transmitted signals so that the multiple access interference at mobile terminals is reduced allowing to transfer the most computational complexity from mobile terminal to the BS. Simulation results are carried out to demonstrate the effectiveness of the proposed preequalization schemes.